A Bridge Between Two Languages: from the enderroc to cascabullo. Miro Villar Rewrites Maria-Merçè Marçal’s Work - Llorca Antolín, FIna (Madrygal. Revista de Estudios Gallegos, 2004)
Starting from a verse by Maria-Merçè Marçal (Catalan poet, 1952-1998), Miro Villar builds one of the sonnets that make up his book Equinoccio de Primavera (1998). This new sonnet is intertextually linked with the original, inspiring one by Marçal. The article tries to globally explore this relationship, taking into account both the author's works and Miro's free interpretation of Marçal's text. Intertextuality, catalonian poetry, galician poetry, remains.